Carbon Capture Potential of Mangrove Ecosystem in Randuboto, Gresik Regency and Its Role in Overcoming Climate Change - Fitriani, Nurina; Hutama, Dio Alif; Isnadina, Dwi Ratri Mitha; Pratama, M Bagas Pramudya; Khadijah, Rafiga; Putranto, Trisnadi Widyaleksono Catur (Journal of Sustainability Perspectives, 2025)
This study examines the carbon capture potential of mangrove ecosystems, focusing on the Randuboto mangrove conservation area. The total biomass in the area amounts to 172.031 tons/ha, with a carbon storage capacity of 80.855 tons/ha and CO2 capture of 296.738 tons/ha. The sapling stratum, characterized by greater mangrove density, produces higher biomass and accommodates more carbon reserves compared to the mature tree stratum. Avicennia marina is identified as the most significant contributor to biomass, carbon storage, and CO2 absorption. Mangroves, through their dense root systems and photosynthetic processes, trap and store carbon both in their biomass and in waterlogged sediments, where decomposition is slowed. Additionally, tidal exchanges enhance carbon capture by promoting the deposition of organic material, further increasing carbon storage in coastal areas. These ecosystems play a crucial role in mitigating climate change by sequestering large amounts of carbon, protecting coastal habitats, and supporting biodiversity, emphasizing the need for their conservation in climate action strategies.